PENGARUH ATRIBUT DESTINASI MICE, CITRA DESTINASI TERHADAP SELEKSI DESTINASI OLEH MEETING PLANNERS DI EXISTING DESTINATION - Etty Khongrat (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
MICE destination attributes are one of the crucial things for Meeting Planners in choosing a destination. This study to purpose and analyze the influence of MICE destination attributes and Destination Image on destination selection. Data collection was carried out by a simple random sampling technique on 165 respondents who were in existing destinations, Jakarta and Bali. The data analysis used in this study is General Structured Component Analysis. The results of this study show that the MICE destination attribute variable has a significant effect on the destination image variable with a path coefficient of with a value (p-value of 0.002 <0.005), this means that the better or complete the MICE destination attribute, the better the image of a destination, then the destination image variable has a significant effect on destination selection with a path coefficient of and a p-value of < 0.001, while the MICE destination attribute variable to the destination selection variable obtained a path coefficent value of with a p-value of 0.202 > 0.05 then there is an insignificant influence, this means that the MICE destination attribute is good or complete does not affect the selection of destinations by Meeting Planners.